Assessing the effect of Working Capital Management on the Business Profitability. - Chesoli, Dr. Joshua Wafula (IJRDO - Journal of Business Management, 2018)
Management of working capital play very essential role in the firm’s profitability. Therefore, this study aims to inquire the impact of working capital management on firm’s profitability. For measuring working capital management inventory conversion period, debtor’s conversion period, creditor’s conversion period, cash conversion cycle, and cash conversion efficiency are taken as independent variables. Firm’s profitability is measured by using the four dependent variables which are net profit margin, return on assets, return on equity, and return on capital employed. Regression analysis is used to discover the impact of working capital management on firm’s profitability by using secondary data. This data is gathered from annual reports of 25 companies listed at NSE for five years from 2008-2012. Manufacturing industry is selected because major portion of total assets contain current assets so working capital management efficiency is necessary in this industry. From results of this study, working capital management has significant impact on firm’s net profit margin, return on assets, and returns on capital employed and insignificant impact is find out on return on equity of firms. Therefore, it is concluded that working capital management has significant impact on firm’s profitability in food sector. It is concluded that if firms in food sector efficiently manage working capital then, firm’s profitability is enhanced. This study also find descriptive statistics which tells how well performance of firms in food sector is and how efficiently these firms are managing working capital.